Fabrication of ultrahigh hydrogen barrier polyethyleneimine/graphene oxide films by LBL assembly fine-tuned with electric field application. (November 2015) - Zhao, Lili; Yuan, Bingbing; Geng, Yiran; Yu, Chunan; Kim, Nam Hoon; Lee, Joong Hee; Li, Peng
Abstract: In this study, layer-by-layer self-assembly of polyethyleneimine (PEI)/graphene oxide (GO) was successfully controlled by an applied electric field. The influences of the applied electric field direction, voltage, and dipping time on the hydrogen barrier properties of PEI/GO self-assembled film were investigated. Ultraviolet–visible light absorption spectroscopy, ellipsometry, atomic force microscopy, and scanning electron microscopy were used to analyze the effects of the electric field on the growth, nanostructure, and micromorphology of the self-assembled film. Results indicated that an applied electric field accelerates the adsorption rate of assembly and increases the GO adsorption quantity. Additionally, such electric field modifies the composite structure of the self-assembled film and spreads out the GO sheets uniformly on the substrate, which results in the formation of a more compact and ordered gas barrier layer with significantly improved hydrogen barrier properties. Higher applied voltage results in a more noticeable field effect. Under 25 V, the hydrogen transmission rate of the PEI/GO self-assembled 10-layer film reached 81 cm 3 /m 2 24 h 0.1 MPa, which was 65% lower than that of standard composite films prepared without using an electric field.